The social nature of serial murder: The intersection of gender and modernity - Wattis, Tanya (2016)
The literature on the aetiology of serial killing has benefited from analyses which offer an alternative perspective to individual/psychological approaches and consider serial murder as a sociological phenomenon. The main argument brought to bear within this body of work identifies the socio-economic and cultural conditions of modernity as enabling and legitimating the motivations and actions of the serial killer. This article interrogates this work from the standpoint of a gendered reading of modernity. Using the Yorkshire Ripper case, it emphasizes how in addition to the political economy, gender relations and masculinity shape the dynamics of serial murder and its representation